Wound healing effects of nanoemulsion containing clove essential oil. (3rd April 2017) - Alam, Prawez; Ansari, Mohammad J.; Anwer, Md. Khalid; Raish, Mohammad; Kamal, Yoonus K. T.; Shakeel, Faiyaz
Abstract: The aim of this study was to investigate the wound healing effects of clove oil (CO) via its encapsulation into nanoemulsion. Optimized nanoemulsion (droplet size of 29.10 nm) was selected for wound healing investigation, collagen determination, and histopathological examination in rats. Optimized nanoemulsion presented significant would healing effects in rats as compared to pure CO. Nanoemulsion also presented significant enhancement in leucine content (0.61 mg/g) as compared to pure CO (0.50 mg/g) and negative control (0.31 mg/g). Histopathology of nanoemulsion treated rats showed no signs of inflammatory cells. These results suggested that nanoemulsion of CO was safe and nontoxic.